A HOLISTIC APPROACH TO THE CONSERVATION OF THE INDUS RIVER DOLPHIN (PLATANISTA MINOR) (OWEN, 1853) - Gachal, Ghulam S; Slater, F M (Biological Sciences - PJSIR, 2002)
The Indus River Dolphin is one of the world ’s most endangered cetaceans with a total population of just a few hundred individuals . Ecological interest in the species was aroused in the 1970’s and intermittent but largely uncoordinated monitoring of numbers has continued ever since. Barrages cutting the river into biologically upstream isolated segments combined with the pressures associated with a growing population in a Third World country pollution such as over-fishing and illiteracy, combine to put the species under threat. The establishment of a Dolphin Reserve between the Guddu and Sukkur barrages in Sindh has made a positive contribution to dolphin conservation but a more holistic approach is advocated here. Accepting that little can be done to change the nature of the barrages, approaches reducing the pollution load of the river water, particularly in low flows, by natural filtration are advocated.